A balanced scorecard for health services in Afghanistan - David H Peters; Ayan Ahmed Noor; Lakhwinder P Singh; Faizullah K Kakar; Peter M Hansen; Gilbert Burnham
The Ministry of Public Health (MOPH) in Afghanistan has developed a balanced scorecard (BSC) to regularly monitor the progress of its strategy to deliver a basic package of health services. Although frequently used in other health-care settings, this represents the first time that the BSC has been employed in a developing country. The BSC was designed via a collaborative process focusing on translating the vision and mission of the MOPH into 29 core indicators and benchmarks representing six different domains of health services, together with two composite measures of performance. In the absence of a routine health information system, the 2004 BSC for Afghanistan was derived from a stratified random sample of 617 health facilities, 5719 observations of patient-provider interactions, and interviews with 5597 patients, 1553 health workers, and 13 843 households. Nationally, health services were found to be reaching more of the poor than the less-poor population, and providing for more women than men, both key concerns of the government. However, serious deficiencies were found in five domains, and particularly in counselling patients, providing delivery care during childbirth, monitoring tuberculosis treatment, placing staff and equipment, and establishing functional village health councils. The BSC also identified wide variations in performance across provinces; no province performed better than the others across all domains. The innovative adaptation of the BSC in Afghanistan has provided a useful tool to summarize the multidimensional nature of health-services performance, and is enabling managers to benchmark performance and identify strengths and weaknesses in the Afghan context.